[OP.3B.06] MEAN SYSTOLIC BLOOD PRESSURE AFTER ADMISSION FOR MYOCARDIAL INFARCTION IS ASSOCIATED WITH ONE YEAR MORTALITY AMONG ELDERLY PATIENTS. (September 2017) - Mouhat, B.; Guenancia, C.; Zeller, M.; Cartigny, G.; Porot, G.; Lorgis, L.; Toucas, C.; Benalia, M.; Rosier, L.; Khalil, C.; Pommier, T.; Cottin, Y.
Abstract : Objective: Optimal blood pressure after acute myocardial infarction (AMI) is still debated. After admission for AMI, the target mean systolic blood pressure (mSBP) is unknown, especially in the elderly patients. Design and method: All patients older than 75 years admitted for AMI in our university hospital from 01/02/2012 to 31/01/2015 were screened to participate at this prospective observational study. Exclusion criteria were cardiogenic shock, end-stage renal disease, less than 3 collected blood pressure values. We completed a one-year follow-up. The primary endpoint was all-cause mortality at one year while additional criteria were major adverse cardiac and cerebrovascular events at one year. The mSBP was defined by the mean of at least 3 measurements over the first 48 hours following admission for AMI. Results: In our population, a ROC curve study on the relationship between mSBP and one-year mortality suggested a cut-off value of mSBP of 125 mmHg. 517 patients (mean age 82 years) were divided into 2 groups according to mSBP (<125 mmHg vs >125 mmHg). There was a higher rate of one year all-cause mortality in the mSBP<125 mmHg group with 58 deaths (22.3%) versus 31 (12.1%)(p = 0, 002) in the mSBP>125 mmHg group, and also an increased cardiovascular mortality in the mSBP<125 mmHg group with 43 deaths (16.5%) versus 22 (8.6%) (p = 0, 006). A multivariate analysis identified 4 independents factors of all-cause mortality at 1 year after AMI: initial GRACE score > 140, LVEF < 40%, history of stroke and mSBP<125 mmHg. Conclusions: Thus, in our elderly AMI population, low mSBP within 48 hours after admission was an independent and powerfull predictor of one-year mortality. Our results raise the question of the timing implying the introduction of usual pharmacological therapies in this high-risk population. Our cut-off of mSBP remains to be validated in further studies.